Systemic inflammatory markers in patients with polyneuropathies - García-Fernández, Patricia; Höfflin, Klemens; Rausch, Antonia; Strommer, Katharina; Neumann, Astrid; Cebulla, Nadine; Reinhold, Ann-Kristin; Rittner, Heike; Üçeyler, Nurcan; Sommer, Claudia (Frontiers in Immunology, 2023)
Introduction In patients with peripheral neuropathies (PNP), neuropathic pain is present in 50% of the cases, independent of the etiology. The pathophysiology of pain is poorly understood, and inflammatory processes have been found to be involved in neuro-degeneration, -regeneration and pain. While previous studies have found a local upregulation of inflammatory mediators in patients with PNP, there is a high variability described in the cytokines present systemically in sera and cerebrospinal fluid (CSF). We hypothesized that the development of PNP and neuropathic pain is associated with enhanced systemic inflammation. Methods To test our hypothesis, we performed a comprehensive analysis of the protein, lipid and gene expression of different pro- and anti-inflammatory markers in blood and CSF from patients with PNP and controls. Results While we found differences between PNP and controls in specific cytokines or lipids, such as CCL2 or oleoylcarnitine, PNP patients and controls did not present major differences in systemic inflammatory markers in general. IL-10 and CCL2 levels were related to measures of axonal damage and neuropathic pain. Lastly, we describe a strong interaction between inflammation and neurodegeneration at the nerve roots in a specific subgroup of PNP patients with blood-CSF barrier dysfunction. Conclusion In patients with PNP systemic inflammatory, markers in blood or CSF do not differ from controls in general, but specific cytokines or lipids do. Our findings further highlight the importance of CSF analysis in patients with peripheral neuropathies.